1977
DOI: 10.1042/cs0520527
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Protein Catabolism after Injury in Man, as Measured by Urinary Excretion of 3-Methylhistidine

Abstract: 1. Urinary excretion of 3-methylhistidine, an index of the rate of muscle breakdown, has been measured during the first 7 days in patients after elective surgery or accidental injury. 2. There was no major difference between the mean daily excretion after skin grafting or total hip replacement, or in injured patients who were hyperketonaemic for the first 24 h after admission. 3. The group of injured patients who did not develop hyperketonaemia had a mean urinary 3-methylhistidine excretion which was twice tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 16 publications
2
29
1
1
Order By: Relevance
“…This hypothesis is supported by the demonstration of decreased glucose production rate in humans (5) and in pigs (6), and a decrease in urinary excretion of nitrogen in fasted human subjects during intravenous infusion off,-hydroxybutyrate (j#-OHB)' (7). Improvement of nitrogen retention in postoperative patients in proportion to their hyperketonemia (8) lends additional support to the hypothesis. 1.…”
Section: Introductionsupporting
confidence: 61%
“…This hypothesis is supported by the demonstration of decreased glucose production rate in humans (5) and in pigs (6), and a decrease in urinary excretion of nitrogen in fasted human subjects during intravenous infusion off,-hydroxybutyrate (j#-OHB)' (7). Improvement of nitrogen retention in postoperative patients in proportion to their hyperketonemia (8) lends additional support to the hypothesis. 1.…”
Section: Introductionsupporting
confidence: 61%
“…It has been shown that patients with traumatic injury and no increase in blood ketones have twice more urine 3-methylhistidine than those with hyperketonemia because they have an excessive muscle protein breakdown (Williamson, 1977). However, Hoover-Plow (1978) found that in rats, after surgery without ketosis, the breakdown occurs in muscle sarcoplasma, where the protein metabolism, mostly catabolism, is augmented, and in myofibrils, where the protein anabolism is depressed.…”
Section: Discussionmentioning
confidence: 99%
“…Severely critically ill and injured patients characteristically demonstrate significant muscle losses and negative nitrogen balance [4][5][6][7][8][9][10][11][12][13][14][15]. The metabolic response to injury is associated with a striking increase in protein catabolism, along with a marked increase in urinary loss of nitrogen, phosphorus, sulfur, potassium, magnesium, and creatinine.…”
Section: Protein and Nitrogen Metabolismmentioning
confidence: 99%